Pasture management and supplemented feed enhanced the performance of farmed buffaloes in Sabah, Malaysia - Saad, Mohd Zamri; Kasim, Azhar; Abu Bakar @ Zakaria, Md Zuki; Abdullah, Punimin (2015)
A buffalo-breeding farm that practices extensive grazing system without supplementation was selected for this study. Farm records between 2004 and 2011 were analyzed for selected parameters, particularly the calving rate, calving interval, daily weight gain of calves and calf mortality. Following the analysis, interventions were implemented in January 2012, which included the increased in pasture area from 399 to 441 acres followed by application of fertilizer. The selected breeder buffaloes were prepared for breeding by supplementing palm kernel cakebased feed at the rate of 1.5kg/animal/day for 2 weeks before breeder males were introduced at the rate of 1 male to 20 females. Prior to the intervention, proximate analysis of pasture revealed 7.6% protein content, 79% of breeder buffaloes were with body score of >3, the average calving rate was 22%, the calving interval was 24±11.2 months, average daily weight gain of calves was 0.89±0.21kg, the average birth weight was 28.31±3.26kg and calf mortality was 26.8±7.0%. Following intervention, proximate analysis of grass revealed 12% crude protein. With feed supplementation, the percentage of breeder female with body score of >3 increased to 95% leading to an average annual calving rate of 50%. Average birth weight was significantly (p<0.05) improved to 35.15±5.39kg while the average daily weight gain was 0.95±0.32kg. Subsequently the average calving interval was reduced to 15.2±9.2 months. Similarly, the calf mortality rate was significantly (p<0.05) reduced to 17.6±4.7%. In conclusion, feeding intervention significantly enhances the performance of farmed buffaloes.